2012
DOI: 10.5923/j.jmea.20120206.08
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Natural Convection around a Circular Cylinder with a Square Cylinder Inside a Square Enclosure

Abstract: Nu merical calcu lations are carried out for natural convection induced by a temperature difference between a cold outer square enclosure and a hot inner cy linder with two different geo metries (i.e. circular and square). A two-dimensional solution for natural convection is obtained, using the finite volu me method for different Rayleigh nu mbers varying over the range of (10 3 -10 5 ). The study goes further to investigate the effect of vertical position of the inner cylinder on the heat transfer and flow fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…For higher length of the obstacle corresponding to LO = 0.4, isotherms and streamlines show a weaker interaction between thermals plumes separated by the obstacle. For this configuration (LO = 0.4), it can be concluded that the behavior of the flow in each region between the obstacle and the cold wall of the enclosure is comparable to that of natural convection in a rectangular confined medium heated from below and symmetrically cooled from sides (Roychowdhury D. G. et al (2002), Goutam S. et al (2007), Paroncini M. et al (2009, Khozeymehnezhad H. et al (2012)).…”
Section: Effect Of the Obstacle Lengthmentioning
confidence: 78%
“…For higher length of the obstacle corresponding to LO = 0.4, isotherms and streamlines show a weaker interaction between thermals plumes separated by the obstacle. For this configuration (LO = 0.4), it can be concluded that the behavior of the flow in each region between the obstacle and the cold wall of the enclosure is comparable to that of natural convection in a rectangular confined medium heated from below and symmetrically cooled from sides (Roychowdhury D. G. et al (2002), Goutam S. et al (2007), Paroncini M. et al (2009, Khozeymehnezhad H. et al (2012)).…”
Section: Effect Of the Obstacle Lengthmentioning
confidence: 78%
“…Buoyancy effects around a circular enclosure contains concentrically heated triangular cylinder has considerable attention by many researchers due to its important practical engineering applications, such as the solar collectors, nuclear reactor applications, cooling of electronic devices, etc [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The outer surface of the enclosure is to reduce the heat transfer from the inner hot surface or to protect the inner body in harsh outdoor environment.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the average heat transfer rate increases with increasing of Rayleigh numbers and nanoparticle volume fraction. Khozeymehnezhad and Mirbozorgi, [9] made a comparison of natural convection around a hot circular cylinder with a hot square cylinder with different locations inside a cooled square enclosure. They showed that the rate of heat transfer from the enclosure which the circular cylinder is located inside is better than square cylinder at the same Rayleigh number.…”
Section: Introductionmentioning
confidence: 99%
“…In numerous investigations [3][4][5][6][7][8][9], an enclosure include obstacles of different geometries (fin, baffle, plate and square or circular body) has been studied by many authors. The main interest in heat transfer is, a heated body should be cooled (For example, electrical chip) or should heat the environment (For example, radiators inside building).…”
Section: Introductionmentioning
confidence: 99%
“…They compared the results of conducting body with adiabatic and neutral isothermic bodies. Khozeymehnez and Mirbozorigi [9] compared the results of natural convection around a circular cylinder with a square cylinder inside a square enclosure.…”
Section: Introductionmentioning
confidence: 99%